A Framework for Introducing Global Health Innovations to the US - Soo Yun Shin; Maria Knight Lapinski; Syed Ali Hussain; Yvens Rumbold; Ruth Osoro; Donald Shell; James W. Dearing (Ubiquity Press, 2022)
Background: Across the globe, there are successful health innovations that could help improve public health in US communities at lower cost and with higher effectiveness than standard practice. However, which factors should be considered to heighten the likelihood of successful transfer of global health ideas to the US still warrants more empirical investigation. Objective: This study aimed to develop a conceptual framework delineating important factors to be considered for successful introduction of global health innovations to US communities, based on diffusion of innovations literature and case studies of global health innovations that have been adopted in US communities. Methods: Five global health innovations adopted in US communities were selected based on expert panel recommendations and a review of academic and gray literatures. These innovations had diverse origins (Columbia, Mexico, South Africa, Sweden, and Wales) and exhibited various means of achieving desired health outcomes. We conducted archival research and 27 interviews (42 interviewees) with leaders and stakeholders of the five innovations to identify important factors for the transfer of global health innovations to the US. Findings: Six factors were determined to be important for global health innovation adoption in the US: (1) innovation attributes, (2) linking agents, (3) inter-organizational partnerships, (4) scale up strategies, (5) implementation processes and outcomes in US communities, and (6) policy and social context. These factors correspond well to factors emphasized in the diffusion of innovation literature, although the importance of some sub-factors (e.g., stigma regarding the origin of innovations) diverged from the literature. Conclusions: Based on our findings, we developed the Designing for Diffusion Framework for Global Health Innovations. The framework provides a comprehensive picture of factors that can be facilitators or hindrances for moving a global health innovation to the US to help smooth the diffusion process for better adoption and implementation in US communities.